High frequency of antimicrobial resistance and virulence gene in Shigella species isolated from pediatric patients in an Iranian Referral Hospital - Mamishi, Setareh; Pourakbari, Babak; Ghaffari Charati, Mohammad; Mahmoudi, Shima; Abdolsalehi, Mohammad Reza; Hosseinpour Sadeghi, Reihaneh (Acta Biomedica Atenei Parmensis, 2022)
Background: Shigella is a main cause of gastroenteritis and it is responsible for 5 to 10 % of diarrhea through the world. The aims of this study were to assess the antibiotic susceptibility pattern and the presence of 3 common virulence genes (sigA, virF, invE) of Shigella strains isolated from patients with gastroenteritis in Children’s Medical Center Hospital, Tehran, Iran. Methods: Over a period of 15 months, all Shigella species collected from the patients with gastroenteritis were entered to the study. Susceptibility testing of all isolates towards different antibiotics was performed using the disk diffusion method and the prevalence of virulence genes was detected by polymerase chain reaction (PCR) technology. Results: Among a total of 183 Shigella strains, 128 Shigella sonnei (70%) and 55 S. flexneri (30%) were isolated. The resistance rate to the antibiotics in S. sonnei strains was higher than S. flexneri. The most sensitive antibiotics for S. flexneri strains were gentamicin (98%), amikacin (85%) and ciprofloxacin (82%), while high resistance rate to trimethoprim-sulfamethoxazole (96%), ampicillin (96%), nalidixic acid (64%) and cefotaxime (60%) was observed. The frequency of invE, virF and sigA gene in S. flexneri strains was 89 %, 93 % and 56 %, respectively; whereas they found in 93 %, 96 %, and 100 % of S. sonnei strains, respectively. SigA gene was identified significantly higher in the S. sonnei strains (100%). There was no significant difference between the presence of virF and invE genes among Shigella strains. Conclusion: The high presence of sigA gene in S. sonnei strains plays an important role in its pathogenesis, and the high frequency of invE and virF genes showed that this classical pathway regulating the expression of Shigella virulence factor genes could play a key role in the pathogenesis of this bacterium.